2002
DOI: 10.1021/ic010876m
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes of Analogues of the Antitumor Antibiotic Streptonigrin

Abstract: The complexes Ru(L1-CH3)(CO)3Cl, RuL2(CO)2Cl2, and RuL3(CO)2Cl2 (L1= 6-methoxy-5,8-quinolinedione, L2 = 7-amino-6-methoxy-5,8-quinolinedione, L3 = 6,6'-dimethoxycarbonyl-2,2'-bipyridine) were prepared by reaction of L1-L3 with the tricarbonyldichlororuthenium(II) dimer. L1-L3 act as bidentates through the ortho oxygen atoms, the pyridyl nitrogen and the adjacent quinone oxygen, and the bipyridyl nitrogens, respectively. RuL3(CO)2Cl2 is characterized by X-ray crystallography. 15N NMR correlation spectra give up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…)314 )73 )238 )17 both ligands bind via the quinoline(N) and the adjacent quinone(O), and are consistent with independent studies of the kinetically inert Ru(II) complexes, where the 1:1 complexes were able to be isolated and fully characterized [27]. When excess metal ion is added to the complex, a second metal ion can bind to the second quinone(O) at C5 and the ether(O) at C6 in both ligands to form M(L)M. This complexation with two metal ions will have two effects.…”
Section: Analogues L 1 and Lsupporting
confidence: 75%
See 2 more Smart Citations
“…)314 )73 )238 )17 both ligands bind via the quinoline(N) and the adjacent quinone(O), and are consistent with independent studies of the kinetically inert Ru(II) complexes, where the 1:1 complexes were able to be isolated and fully characterized [27]. When excess metal ion is added to the complex, a second metal ion can bind to the second quinone(O) at C5 and the ether(O) at C6 in both ligands to form M(L)M. This complexation with two metal ions will have two effects.…”
Section: Analogues L 1 and Lsupporting
confidence: 75%
“…Higher DNA strand cleavage, which would correlate with more DNA damage, may translate to beneficial anticancer activity. The results of this work, and related studies with Ru(II) [27], suggest that metal complexes of SN and SN analogues containing the 2,2 0 -bipyridyl binding site will accelerate the rate of DNA cleavage compared to the free drug. The hypoxia in solid tumors, which would increase the concentration of SN ÅÀ compared to normal cells may be an important factor related to the chemistry shown in Fig.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The complexes Ru(L1-CH 3 )(CO) 3 Cl, RuL2(CO) 2 Cl 2 , and RuL3(CO) 2 Cl 2 (L1 = 6-methoxy-5,8-quinolinedione, L2 = 7amino-6-methoxy-5,8-quinolinedione, and L3 = 6,6'dimethoxycarbonyl-2,2'-bipyridine) have been prepared by reaction of L1, L2, and L3, respectively, with the tricarbonyldichlororuthenium(II) dimer [389]. L1, L2, and L3 act as bidentate ligands through the ortho O atoms, the pyridyl nitrogen and the adjacent quinone oxygen, and the bipyridyl nitrogens, respectively, RuL3(CO) 2 Cl 2 was characterized by X-ray crystallography.…”
Section: Metal Complexationmentioning
confidence: 99%
“…It is interesting to compare the twisted arrangement of the dimethyl 2,2 H -bipyridine-6,6 H -dicarboxylate ligand in (II) with previously reported examples. Two NÐCÐCÐN torsion angles of 10.4 (5) and 25.1 (6) are observed for these ligands in complex (II), revealing a signi®cantly greater twist than observed in the three structures of metal complexes of dimethyl 2,2 H -bipyridine-6,6 H -dicarboxylate (Anderberg et al, 2002;Kinnunen et al, 2000Kinnunen et al, , 2002 reported prior to this study (average CÐNÐNÐC torsion angles of ca 5 ). The twist in (II) is also greater than that observed in bis(2,2 H -bipyridine)copper(I) tri¯uoromethanesulfonate (Tomislav, 2006) and the analogous perchlorate salt (Munakata et al, 1987), in which the 2,2 H -bipyridine ligands remain essentially planar, with average CÐNÐNÐC torsion angles of 2.9 and 1.8 , respectively.…”
Section: Commentmentioning
confidence: 46%